Kína energiabiztonsága és a BRI - Horváth, Csaba Barnabás (Távol-keleti Tanulmányok, 2018)
This paper examines the question how the One Belt One Road initiative impacts the issue of energy security for China. The OBOR initiative covers virtually all geographic areas where key energy supply routes of China are located, from sea lanes to existing and planned overland pipelines. Many of these regions are, however, scenes of great-power rivalry for geopolitical influence between China and other great and middle powers. Among such routes we can mention overland pipelines carrying gas and oil from Central Asia, as well as strategic sea lanes, such as the Straits of Malacca, where virtually all oil imported from the Middle East passes through. This paper endeavours to investigate how these rivalries impact the objectives of the OBOR initiative and the energy security of China, also making distinctions which supply routes China will likely be able to secure the most and which the least.